LB3D: A parallel implementation of the Lattice-Boltzmann method for simulation of interacting amphiphilic fluids - Schmieschek, S.; Shamardin, L.; Frijters, S.; Krüger, T.; Schiller, U.D.; Harting, J.; Coveney, P.V. (Computer physics communications, 2017)
We introduce the lattice-Boltzmann code LB3D, version 7.1. Building on a parallel program and supporting tools which have enabled research utilising high performance computing resources for nearly two decades, LB3D version 7 provides a subset of the research code functionality as an open source project. Here, we describe the theoretical basis of the algorithm as well as computational aspects of the implementation. The software package is validated against simulations of meso-phases resulting from self-assembly in ternary fluid mixtures comprising immiscible and amphiphilic components such as water–oil–surfactant systems. The impact of the surfactant species on the dynamics of spinodal decomposition are tested and quantitative measurement of the permeability of a body centred cubic (BCC) model porous medium for a simple binary mixture is described. Single-core performance and scaling behaviour of the code are reported for simulations on current supercomputer architectures. Program Title: LB3D Program Files doi:http://dx.doi.org/10.17632/9g9x2wr8z8.1 Licensing provisions: BSD 3-clause Programming language: FORTRAN90, Python, C Nature of problem: Solution of the hydrodynamics of single phase, binary immiscible and ternary amphiphilic fluids. Simulation of fluid mixtures comprising miscible and immiscible fluid components as well as amphiphilic species on the mesoscopic scale. Observable phenomena include self-organisation of mesoscopic complex fluid phases and fluid transport in porous media. Solution method: Lattice-Boltzmann (lattice-Bhatnagar–Gross–Krook, LBGK) [1, 2, 3] method describing fluid dynamics in terms of the single particle velocity distribution function in a 3-dimensional discrete phase space (D3Q19) [4, 5, 6]. Multiphase interactions are modelled using a phenomenological pseudo-potential approach [7, 8] with amphiphilic interactions utilising an additional dipole field [9, 10]. Solid boundaries are modelled using simple bounce-back boundary conditions and additional pseudo-potential wetting interactions [11]. Additional comments including Restrictions and Unusual features: The purpose of the release is the provision of a refactored minimal version of LB3D suitable as a starting point for the integration of additional features building on the parallel computation and IO functionality. [1]S. Succi, The Lattice Boltzmann Equation: For Fluid Dynamics and Beyond, Oxford University Press, 2001.[2]B. Dünweg, A. Ladd, Lattice Boltzmann simulations of soft matter systems, Adv. Poly. Sci. 221 (2009) 89–166[3]C. K. Aidun, J. R. Clausen, Lattice-Boltzmann Method for Complex Flows, Annual Review of Fluid Mechanics 42 (2010) 439.[4]X. He, L.-S. Luo, A priori derivation of the lattice-Boltzmann equation, Phys. Rev. E 55 (1997) R6333.[5]X. He, L.-S. Luo, Theory of the lattice Boltzmann method: from the Boltzmann equation to the lattice Boltzmann equation, Phys. Rev. E 56.[6]Y. H. Qian, D. D’Humiéres, P. Lallemand, Lattice BGK Models for Navier–Stokes Equation, Europhysics Letters 17 (1992) 479.[7]X. Shan, H. Chen, Lattice-Boltzmann model for simulating flows with multiple phases and components, Physical Review E 47 (1993) 1815.[8]X. Shan, G. Doolen, Multicomponent lattice-Boltzmann model with interparticle interaction, Journal of Statistical Physics 81 (1995) 379.[9]H. Chen, B. Boghosian, P.V. Coveney, M. Nekovee, A ternary lattice-Boltzmann model for amphiphilic fluids, Proceedings of the Royal Society of London A 456 (2000) 2043.[10]M. Nekovee, P. V. Coveney, H. Chen, B. M. Boghosian, Lattice-Boltzmann model for interacting amphiphilic fluids, Phys. Rev. E 62 (2000) 8282.[11]N. S. Martys, H. Chen, Simulation of multicomponent fluids in complex three-dimensional geometries by the lattice-Boltzmann method, Phys. Rev. E 53 (1996) 743.